Assess and Measure Retentions Rates Through Satisfaction - Ikhwanul Hakim,; Widagdo, Suwignnyo; Handayani, Yuniorita Indah (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2021)
The success of a college depends on how much retention is formed and student satisfaction is an important factor in achieving that retention. The purpose of this study was to examine the effect of institutional image, service quality, price perception, on student retention through student satisfaction. A total of 100 STIE Widya Gama Lumajang students participated as respondents in this study. Structural Equation Model based on SmartPls 3.0 is used to test the proposed hypothesis. The results showed that there was no direct effect of institutional image and price perception on student retention and price perception had no effect on student satisfaction. Based on its practical implications, student satisfaction has an important mediating role on the influence of institutional image and service quality which is assessed by students to encourage willingness to stay and complete their studies until graduation at STIE Widya Gama Lumajang and student satisfaction. does not have an important mediating role on the effect of price perception on student retention.